2011
DOI: 10.4028/www.scientific.net/kem.493-494.175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TCP Loaded Clinoptilolite Use as Graft Material on Rabbit Tibia

Abstract: Clinoptilolite mineral which is a member of zeolite family has been recently used in medical and dental applications. Until today, it has never been used as a graft material. In the present study tricalcium phosphate (TCP) imbued 90-95% pure clinoptilolite was used as graft in rabbit tibia. General anesthesia was accomplished using intra muscular (IM) injections of Xylazin and Ketamine HCL. TCP imbued clinoptilolite was placed in the defects created in the tibias of the subjects. Control group defects were lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Clinoptilolite (CLIN) is known as the world’s most abundant natural zeolite. , It is biocompatible and therefore widely used for detoxification of organisms, , drug delivery , (e.g., release of antibiotics), or fabrication of biosensors. , Moreover, CLIN demonstrated antitumoral, antioxidant, antiapoptotic, and anti-inflammatory activities. , Uyumaz et al showed by in vivo studies that CLIN mixed with pharmaceutical-grade tricalcium phosphate does not induce any inflammatory processes in rabbits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinoptilolite (CLIN) is known as the world’s most abundant natural zeolite. , It is biocompatible and therefore widely used for detoxification of organisms, , drug delivery , (e.g., release of antibiotics), or fabrication of biosensors. , Moreover, CLIN demonstrated antitumoral, antioxidant, antiapoptotic, and anti-inflammatory activities. , Uyumaz et al showed by in vivo studies that CLIN mixed with pharmaceutical-grade tricalcium phosphate does not induce any inflammatory processes in rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Moreover, CLIN demonstrated antitumoral, 35 antioxidant, antiapoptotic, and anti-inflammatory activities. 36,37 Uyumaz et al 38 showed by in vivo studies that CLIN mixed with pharmaceutical-grade tricalcium phosphate does not induce any inflammatory processes in rabbits.…”
Section: ■ Introductionmentioning
confidence: 99%
“…El-shenawy et al have successfully used Cpt as a coating material for nano-porous titanium implant and reported that Cpt did not adversely affect the cell culture viability and exhibited high corrosion resistance in comparison with bare porous titanium implant [24]. Uyumaz et al fabricated a tricalcium phosphate (TCP)-Cpt composite to repair defects in rabbit tibia, their results highlighted the importance of Cpt supporting structure in tibia remodelling process [25]. Synthetic zeolite (type: Y)-HA composites prepared by Iqbal et al showed good bioactivity and compatibility [26].…”
Section: Introductionmentioning
confidence: 99%